2021
DOI: 10.1002/ecs2.3836
|View full text |Cite
|
Sign up to set email alerts
|

A model comparison of fire return interval impacts on carbon and species dynamics in a southeastern U.S. pineland

Abstract: Ecosystem process models can be used to predict forest response to disturbances at a range of scales. Selection of the spatial class of model should depend on the scale of the research or management question, and model type should depend on the ecosystem attributes of interest. In some cases, multiple classes of models could be used to address a single research question, with evaluations at each scale having potential benefits and drawbacks. This study examines two classes of models relative to how fire return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 99 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…While these stands contain more C in competing woody vegetation, they have a higher risk of catastrophic wildfire than naturally regenerated longleaf pine stands managed with prescribed fire. Researchers used forest landscape models to compare C outcomes among prescribed fire exclusion, prescribed fire, and wildfire scenarios [11,12]. These studies indicated that prescribed fire scenarios resulted in lower C emissions and greater aboveground biomass over time compared to wildfire scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…While these stands contain more C in competing woody vegetation, they have a higher risk of catastrophic wildfire than naturally regenerated longleaf pine stands managed with prescribed fire. Researchers used forest landscape models to compare C outcomes among prescribed fire exclusion, prescribed fire, and wildfire scenarios [11,12]. These studies indicated that prescribed fire scenarios resulted in lower C emissions and greater aboveground biomass over time compared to wildfire scenarios.…”
Section: Introductionmentioning
confidence: 99%